(untitled) (Economic studies journal, 2021)
Abstract The main aim of this study is to estimate the asymmetric effects of oil GDP on CO2 emissions in Libya during the period 1962-2017. In order to achieve its objective, the study adopted the Non-linear Autoregressive Distributed Lag NARDL model. According to cointegration test results, the study supported the existence of a long run equilibrium relationship between its variables. In addition, it showed that the negative changes in oil GDP in the current year positively affect CO2 emissions in the short run. However, the lag one of the changes in oil GDP is found to be negatively affect CO2 emissions in the short run too. Furthermore, long run coefficients indicated that positive and negative changes in oil GDP positively impact CO2 emissions in Libya.